Work From Home Dimasa Pandemi, Efektifkah ? - Tuwinanto Tuwinanto; Dedi Rianto Rahadi (Universitas Pendidikan Nasional, 2021)
The government policy in suppressing the spread of the covid-19 virus continues to be carried out, the office and factory cluster is one that is very worrying so that the government and companies work together to provide a way out so that operational activities can continue so that the economic condition of the community is maintained by prioritizing employee safety factors and his family. The research objective was to determine whether work from home during a pandemic was an effective solution?. The research method is carried out with a qualitative approach. The results showed that work from home is one of the most ideal work methods during this pandemic season, because it can reduce employee exposure to the virus in the workplace or office.